BUSINESS DEVELOPMENT OF GRAPHIC DESIGN AND EDITING SERVICES KARACAK DESIGN BASED ON THE SWOT ANALYSIS AND FEASIBILITY STUDY METHOD: PENGEMBANGAN USAHA JASA DESAIN GRAFIS DAN EDITING KARACAK DESIGN BERDASARKAN METODE ANALISIS SWOT DAN FEASIBILITY STUDY - Rizki Maulana; Susinah Kuntadi (The Asia Pacific Journal Of Management Studies, 2024)
This research was conducted with the aim of finding out the feasibility of the Karcak Design design and editing services business in terms of market and marketing aspects, operational aspects, HR management aspects and legal aspects using qualitative descriptive methods, while financial aspects were analyzed using quantitative descriptive methods with a manual system with the help of the program Microsoft Excel. The analysis results obtained from market and marketing aspects, technical aspects, HR management aspects and legal aspects, Karcak Design's design and editing services can still be said to be feasible to run, but there are several things that need to be evaluated from the marketing aspect related to promotional activities that are not consistent and only relying on the Instagram feature alone so that the market share absorbed is still not according to the desired target, apart from that, from the HR management aspect, Karcak Design does not yet have a partner/team. Meanwhile, the results of the financial aspect analysis show that Karcak Design's design and editing services are feasible. This can be seen from the NPV (Net Present Value) which is > 0 and has a positive value, namely IDR 45,035,214. The Profitability Index (PI) obtained was > 1, namely 6.751.